Isorhamnetin inhibited the proliferation and metastasis of androgen-independent prostate cancer cells by targeting the mitochondrion-dependent intrinsic apoptotic and PI3K/Akt/mTOR pathway. Issue 3 (18th March 2020) - Cai, Fangzhen; Zhang, Yanmei; Li, Jianwei; Huang, Sihuai; Gao, Ruilin
Abstract: The present study investigated the effects of Isorhamnetin on two types of prostate cancer cells (androgen-independent and androgen-dependent) and explored its possible mechanisms underlying such effects. Treatment with Isorhamnetin significantly inhibited cell growth and induced lactate dehydrogenase (LDH) release of androgen-independent DU145 and PC3 prostate cancer cells, but exhibited almost no toxicity effect on androgen-dependent LNCaP prostate cancer cell line or normal human prostate epithelial PrEC cells, which was achieved by the induction of apoptosis in a mitochondrion-dependent intrinsic apoptotic pathway. Furthermore, Isorhamnetin inhibited cell migration and invasion in concentration-dependent manners by enhancing mesenchymal−epithelial transition (MET) and inhibiting matrix metalloproteinase (MMP) 2 (MMP-2) and MMP-9 overexpression. In addition, Isorhamnetin also down-regulated the expression of phosphorylated PI3K (p-P13K), Akt (p-Akt), and mTOR (p-mTOR) proteins in both cancer cells, revealing Isorhamnetin to be a selective PI3K–Akt–mTOR pathway inhibitor. In summary, these findings propose that Isorhamnetin might be a novel therapeutic candidate for the treatment of androgen-independent prostate cancer.